Multicomponent conjugate heat and mass transfer in biomass materials during microwave pyrolysis for biofuel production - Motasemi, F.; Gerber, A.G. (Fuel (Guildford), 2018)
[Display omitted] •A CFD model is developed to describe the microwave pyrolysis in biomass pellets.•A modeling approach is presented to incorporate the main features of the process.•The developed CFD model can be applied into different bio-conversion processes.•Temperature is a key element to optimize the biofuel yield and energy consumption.•Probe location can be the main obstacle for experimental validation. The aim of this paper is to investigate the heating behavior of biomass materials under microwave pyrolysis process. A detailed computational fluid dynamics (CFD) model is developed based on the finite volume method using ANSYS CFX (14.0) software to describe the heat and mass transfer during the microwave processing of biomass pellets. The article presents a modeling approach for incorporating the basic fundamentals of microwave pyrolysis process in the form of source terms for mass, momentum, heat and species into the general transport equations for nitrogen and volatiles in the gas phase and wood and bio-char in the solid phase. The model covers the complex coupling between several key elements of the process including microwave heating, pyrolysis kinetics, phase change, rapid variation in mixture properties and gas phase transport. The developed CFD model is validated through the experimental trials in a custom-built microwave pyrolysis unit. The model predicts the maximum temperature, temperature rates and temperature profiles during the process. Close agreement is obtained between the results obtained from the experiments and simulations. It was found that the biomass temperature is affected by the microwave absorbed power which is a function of biomass mixture properties and the released volatile during the process. The results also indicated that increase in microwave power level increases the maximum obtained temperature; however, the amount of absorbed power within the material decreases significantly in higher temperature levels. As temperature and power requirement are vital factors in making microwave processing viable, a useful CFD tool that provides this information could be invaluable for industry.